Students' Critical Reading Ability Toward News on TikTok Social Media - Kamilatul Asfiya’; Amiroh Khoirun Jidda; Tri Ratna Puspitasari; Nur Fadhilah Rahmadhani; Neni Dwi Agustin; Trinil Dwi Turistiani (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
The development of social media has made TikTok not only a platform for entertainment but also a source of information for students. The ease of accessing information through short videos on TikTok allows news to spread rapidly, including information that is not necessarily accurate, making critical reading skills essential for students. This study aims to describe students’ critical reading abilities toward news on TikTok social media, including the ability to identify main ideas, distinguish facts from opinions, evaluate source credibility, and recognize hoax and clickbait news. This research employed a descriptive quantitative method involving 41 students from various universities in Indonesia as respondents. Data were collected through an online questionnaire distributed via Google Forms, consisting of Likert-scale statements, multiple-choice questions, and short essay questions, and were analyzed descriptively using percentages. The results showed that the intensity of TikTok use among students is very high, and most respondents frequently obtain information through the platform. However, the majority of students demonstrated fairly good critical reading skills, such as checking news sources, comparing information with other media, recognizing clickbait characteristics, and being more careful before sharing news. Factors influencing students’ critical reading abilities include digital literacy levels, information verification habits, experiences with hoax news, and the influence of sensational headlines. Therefore, critical reading skills play an important role in helping students filter and understand digital information more wisely and rationally in the social media era.